Flavin-adenine-dinucleotide gold complex nanoparticles: chemical modeling design, physico-chemical assessment and perspectives in nanomedicine. Issue 21 (23rd September 2021) - Arib, Celia; Bouchemal, Nadia; Barile, Maria; Paleni, Didier; Djaker, Nadia; Dupont, Nathalie; Spadavecchia, Jolanda
Abstract : Flavin-adenine-dinucleotide gold complex nanoparticles: from modeling design (A) to schematic hypothesis of intercalation between DNA strands (B). Abstract : Flavoproteins play an important role in the regulatory process of cell life, and they are involved in several redox reactions that regulate the metabolism of carbohydrates, amino acids, and lipids. The development of effective drug delivery systems is one of the major challenges in the fight against cancer. This study involves a nanomedicine pathway to encapsulate the cofactor flavin adenine dinucleotide (FAD) using polymeric gold nanoparticles (PEG-AuNPs) through two chemical methods of functionalization (chelation (IN); carbodiimide chemistry (ON)). These hybrid gold nanoparticles and their precursors were characterized by analytical techniques (Raman, UV-Vis, and H 1 -NMR spectroscopy and transmission electron microscopy (TEM)) which confirmed the grafting of the cofactor agent. The results of the computational studies (Density Functional Theory (DFT)) were in agreement with the experimental observations. We also monitored the interaction of our hybrid nanoparticle systems with small aptamers (APT) in order to validate the hypotheses on the biomolecular mechanisms and also investigate their biological efficiency on pancreatic cancer cells (MIAPaCa-2 cells).